Phytochemical constituents and the distribution of Oxycarotenoids in dehydratedgreen leafy Vegeteables of different sources - SHERENA P A,; P T ANNAMALA,; J K MUKKADAN, (International Journal of Pharma and Bio Sciences, 2017)
Plants possess many phytochemicals such as carotenoids, ascorbic acid,a-tocopherol, flavonoids, chlorophylls and polyphenols, etc. Green vegetables are packed with antioxidants, nutrients and fibers. These are essential for maintaining various biochemical processes including reducing levels of LDL-cholesterol, improving vision, helping to manage weight and boosting immunity. This study was undertaken to determine the total content of polyphenols, flavanoids, chlorophylls and xanthophylls in 15 different leafy vegetables from different regions by spectrophotometric method.The distribution of major oxycarotenoids such as lutein, zeaxanthin and β-cryptoxanthin was also studied using high performance liquid chromatography. The analytical data showed that the total polyphenol content ranged from 0.79-7.3 g/100g;total flavonoid content ranged from 1.1-23.7 g/100g;total chlorophyll content ranged from 0.47-4.7g/100g and the total xanthophyll content ranged from 0.17-1.65g/100g.In the oxycarotenoid distribution the results showed that lutein content of leafy vegetables ranged from 0.03-0.64 g/100g.The analysis also showed the presence of zeaxanthin and β-cryptoxanthin in some leaves like coriander curry leaf, fenugreek(methi) and mint leaves.Furthermore, we can conclude that the selected 15 different leafy vegetables are nutritionally and medicinally important and those of Indian sources are rich in xanthophylls whereas of Egyptian sources are rich in polyphenols and flavanoids